Violencia de Estado e identidades políticas. Argentina durante el Proceso de Reorganización Militar (1976 –1983) - Sebastián Barros (Amnis)
This paper analyses the consequences of two discursive structures present in the discourse of Argentina's last dictatorship between 1976 and 1983. From the point of view proposed here, the military government provoked certain changes in the Argentinean social and economic structure that influenced the consequent emergence of new hegemonic practices. These changes weresupported by two elements of the dictatorship's discourse, the discourse of the « dirty war » and the discourse of the « free market ». Both discourses guided the actions of the military government and their consequences contributed to the weakening and fragmentation of traditional political identities. The theoretical framework is based on the work of Ernesto Laclau and Chantal Mouffe.